Growth and productivity of different intercrops grown under gamhar (Gmelina arborea) based agroforestry system - Vanlalngurzauva, T.; Dhara, P.K.; Banerjee, H.; Maiti, S. (Indian Journal of Agroforestry, 2020)
Field experiments were conducted during the kharif seasons of 2005 and 2006 at Regional Research Station (Red and Laterite Zone), Bidhan Chandra Krishi Viswavidyalaya, Jhargram, Paschim Medinipur, West Bengal. Rice, cowpea, groundnut and blackgram were intercropped with 14-years old gamhar (Gmelina arborea) plantation to study the growth and productivity of these intercrops and their effect on the growth of tree. Results revealed that the yields of all the intercrop were 1.97, 1.03, 0.69 and 0.46 t ha-1 (for rice, cowpea, groundnut and blackgram respectively). However, the return from the crop was highest (Rs. 13,800.00 ha-1 year-1) with blackgram or groundnut and lowest from cowpea (Rs. 6,180.00 ha-1 year-1). Growth of gamhar was influenced due to intercropping with legume intercrops (blackgram, groundnut and cowpea). The tree height, dbh and volume yield of gamhar was observed highest when intercropped with blackgram (8.35 m, 16.78 cm and 5.27 m3 ha-1 year-1, respectively) closely followed by gamhar + groundnut intercropping (8.30 m, 16.54 cm and 5.09 m3 ha-1 year-1, respectively) and lowest with gamhar + rice intercropping (7.34 m, 15.70 cm and 4.22 m3 ha-1 year-1, respectively).